Insuficiencia respiratoria grave por gripe h1n1: presentación de un caso fatal - Jorge A. Vázquez; Silvina Borello; Fernando Saldarini; María Cecilia Rodríguez; Daniel N. Chiacchiara; Gabriel G. Carqueijeda-Román (Revista del Hospital Italiano de Buenos Aires)
-